2011
DOI: 10.1007/s11999-010-1738-1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Ideas: Treatment of Precollapse Osteonecrosis Using Stem Cells and Growth Factors

Abstract: Background Osteonecrosis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
(61 reference statements)
0
30
0
2
Order By: Relevance
“…Because these typically “pro-regenerative” MP subpopulations predominate the SS as early as day 7, increasing their recruitment may offer only modest therapeutic efficacy for muscle degeneration, which occurs over weeks. A more promising strategy may be to bias recruited cells toward pro-regenerative cytokine secretion using appropriately engineered delivery of immune modulatory molecules[44], [49], [50]. …”
Section: Discussionmentioning
confidence: 99%
“…Because these typically “pro-regenerative” MP subpopulations predominate the SS as early as day 7, increasing their recruitment may offer only modest therapeutic efficacy for muscle degeneration, which occurs over weeks. A more promising strategy may be to bias recruited cells toward pro-regenerative cytokine secretion using appropriately engineered delivery of immune modulatory molecules[44], [49], [50]. …”
Section: Discussionmentioning
confidence: 99%
“…Growth factors are critical for osteoinduction, a central process for bone repair, as occurs in fracture healing. To ensure successful bone healing, the induction of angiogenesis is needed, and marrow stromal cells (MSCs) are also used to induce bone formation (15–20). Mesenchymal elements express factors like Vascular Endothelial Growth Factor (VEGF), and it has been demonstrated that MSCs from healthy subjects are characterized by a signature profile of VEGF expression distinct from patients affected by Osteonecrosis (ON) of the hip and by Osteoarthritis (OA) (14).…”
Section: Endothelial and Bone Cells The Molecular Basis Of Their Intmentioning
confidence: 99%
“…This phenomenon led to a lack of osteogenesis and revascularization may contribute to the insufficient reconstruction repair after CD. For this reason, local application of stem cells may be one of the solutions [28]. BMMCs are highly enriched with BMMSCs in terms of fibroblast colony-forming units [10].…”
Section: Discussionmentioning
confidence: 99%